Factors Impacting Talent Retention: Case of Indonesia - Tambunan, Vebrina Anggraini; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research examines the influence of HRM Practices, Positive Emotions, and Knowledge Management on Employee Attachment, as well as the influence of Employee Attachment on Talent Retention in the oil and gas industry in Indonesia. The unit of analysis in this research is employees in the oil and gas industry, using causal relationship models and cross-sectional data methods. The variables tested include HRM Practices, Positive Emotions, Knowledge Management, Employee Attachment, and Talent Retention, which are measured with an interval scale using a Likert scale of 1-5. Data was collected through a Google Forms questionnaire distributed via WhatsApp and Instagram to employees of PT. Donggi Senoro LNG (DSLNG), JGC Indonesia (JIND), JOB Pertamina Medco E&P Tomori Sulawesi (JOB Group), and other oil and gas companies, used a purposive sampling technique. Data collection was conducted from June 3, 2024, to July 5, 2024, resulting in 268 respondents with 230 valid responses. The research results show that HRM Practices do not positively affect Employee Attachment, indicating that the increase in HRM Practices perceived by employees has no significant influence on their level of attachment. On the other hand, Positive Emotions and Knowledge Management were found to positively affect Employee Attachment. This confirms that the higher the level of Positive Emotions and Knowledge Management possessed by employees, the higher their attachment to the company. Additionally, Employee Attachment has been proven to have a positive effect on Talent Retention, showing that the higher the employee attachment, the higher the level of talent retention in Indonesia's oil and gas companies. These findings provide important insights for companies in designing strategies to increase employee engagement and retention.